Analysis of Arabica Coffee Characteristics and Drying Method on Arabica Coffee Flavor Using Analysis of Variance - Sumitro, Martinus Robinson; Hutabarat, Julianus; Achmadi, Fuad (LPPM of NAROTAMA UNIVERSITY, 2024)
Purpose: This study investigated the effect of the coffee drying process using a coffee drying house on the moisture content, acidity, caffeine value, and flavor of arabica coffee. Design/methodology/approach: An experimental method with a two-factor analysis of variance was used to evaluate significant differences between three different drying processes: Before Drying Process, Sun Drying Process, and Drying Process with Coffee Drying House Findings: The results showed that sun-drying coffee with a coffee drying house produced coffee with lower moisture content, acidity, and caffeine value compared to the other drying processes Research limitations/implications: The research location was Karot Village, Langke Rembong Subdistrict, Manggarai Regency. The object of research was the drying process of arabica coffee beans and the measurement of moisture content, acidity content and caffeine content of arabica coffee. The method used was analysis of variance with a fixed model (one-way anava design, block subsampling anava and two-factor anava). The data obtained were the acidity value, caffeine value, moisture content and coffee flavour. Practical implications: The results of the research were successful and improved the quality of coffee exports in Karot Village, Langke Rembong District, Manggarai Regency. Originality/value: The research carried out by the researcher states that this research is the result of his work and is the first time at Karot Village, Langke Rembong District, Manggarai Regency with the title of the research being researched, except for quotations from several summaries, all of which the researcher has explained the source. Paper type: Research Paper